The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.18203/2394-6040.ijcmph20173633
|View full text |Cite
|
Sign up to set email alerts
|

A study of factors affecting the knowledge of Janani Shishu Suraksha Karyakram among health workers in rural block Shirur of Pune district, Maharashtra

Abstract: Background: Government of India launched the Janani Shishu Suraksha Karyakram (JSSK) on 1st June 2011, a new national initiative, to make better health facilities for women and child. The scheme is estimated to benefit more than 12 million pregnant women who access govt. health facilities for their delivery. The objective was to study the factors affecting the knowledge of Janani Shishu Suraksha Karyakram (JSSK) among health workers in rural block Shirur.Methods: A cross-sectional study was conducted among hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Still, there was no substantial evidence to suggest that the JSY was associated with a reduction in neonatal or early neonatal mortality. Jadhav et al (2017) studied factors affecting the knowledge of JSSK among health workers and found that gender and training have a critical association with knowledge about JSSK. Dhiman et al (2017) suggested improving the quality of antenatal communication and strengthening the awareness about the same with expectant mothers.…”
Section: Intervention Programmementioning
confidence: 99%
“…Still, there was no substantial evidence to suggest that the JSY was associated with a reduction in neonatal or early neonatal mortality. Jadhav et al (2017) studied factors affecting the knowledge of JSSK among health workers and found that gender and training have a critical association with knowledge about JSSK. Dhiman et al (2017) suggested improving the quality of antenatal communication and strengthening the awareness about the same with expectant mothers.…”
Section: Intervention Programmementioning
confidence: 99%